Risk of hypospadias due to use of Pesticides among the rural families of Haryana, Uttar Pradesh and Bihar in India: An AIIMS-Delhi study highlighting the risk on agriculture produce in Pregnant Mothers & the importance of regulatory controls in the prevention of Birth Defects in Children - Minu Bajpai (National Board of Examinations Journal of Medical Sciences, 2023)
Introduction: The potential risk of hypospadias in children born to mothers living close to agricultural area where pesticides are used has been a topic of interest in scientific research. The present study aimed to analyze the risk of hypospadias in families living under the direct exposure to pesticide and families living under no direct exposure of pesticides. Material & Methods: The present study includes 129 patients with hypospadias who underwent reconstructive surgery by a single surgeon single institution. The odds ratio (OR) of hypospadias risk has been calculated with common controls. All the patients divided in two groups one with direct exposure to pesticide i.e. farmers and other is no direct exposure i.e. profession other than farming. Results: The ORs were consistently greater in group 1, indicating an increased risk of hypospadias. Patients with direct exposure to pesticides showed a significantly higher OR when compared to patients without direct exposure to pesticides and common controls. Conclusion: The study found a significant association between hypospadias occurrence and pregnant mothers' with direct exposure to the pesticide. The OR was greater than 1 with highly significant p value of <0.001. The fall out of this study has serious implication on agriculture produce, particularly of interest would be designing further studies on tea plantations, vineyards & beer manufacturing units.